Real-Time Polymerase Chain Reaction for Detection of Strongyloides stercoralis in Stool - Sultana, Yasmin (The American Society of Tropical Medicine and Hygiene, 2013)
The use of real-time polymerase chain reaction (PCR) for detection of Strongyloides stercoralis in stool has recently been described. We compared five DNA extraction methods by using normal human stool spiked with Strongyloides ratti and tested by using a real-time PCR. The PowerSoil kit was found to be the best technique in terms of sensitivity and ease of use. The PCR detected DNA extracted from one spiked S. ratti larva diluted 10(−2). The PowerSoil kit was then used to extract DNA from 160 human survey samples. All culture positive specimens with a high and moderate larval load were identified by real-time PCR, but only 15% of specimens with low larval load were positive. Specificity was greater than 99%. The combination of the PowerSoil kit and real-time PCR reliably detected high to moderate larval numbers of S. stercoralis in stools but was less sensitive when the larval load was low.